Politics Communication Based on Local Cultural Branding: A Critical Ethnographic Study of Cultural Festivals in Lamongan Regency - Prayogo, Moh. Dey; Kusumaningrum, Herlina (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2025)
In 2023, the Lamongan Regency government released a schedule of 39 cultural festivals held from March to December. The Regent of Lamongan's involvement in each event, from the promotional stage, where his image was prominently featured on posters and billboards, to the implementation stage, where he was given a dedicated time and platform to address the public directly, is crucial for examining the underlying message behind these cultural festival programs and the extent to which the local government has developed and successfully implemented a local cultural branding program to promote Lamongan's local cultural wisdom without any political bias. This research aims to uncover the hegemony of power from a political communication perspective through an examination of the cultural festivals held. A qualitative approach using critical ethnography methods positions and embeds culture within a broader symbolic, social, economic, political, and historical context, rather than simply seeking recognition from its members. The research results indicate that cultural festivals serve as a form of political legitimacy by integrating local identity, promoting public participation, protecting heritage, and fostering economic empowerment. Political communication strategies encompass verbal, non-verbal, mass media, digital, and cultural forms, which are integrated to create an image of leadership that cares about regional culture. Future research could focus on countering hegemony through populist practices in festivals, both at the local and national levels. This could include delving deeper into how community groups, artists, cultural communities, academics, and activists construct counter-spaces against the dominant discourses and symbols of power reproduced through festivals.